Reproductive Intentions and Fertility Preservation Among Transgender and Nonbinary Individuals: A Cross-Sectional Study in Brazil - Letícia A. Mendonça; Isabela G. Silva; Iris T.T. Umeda; Phelipe E. Silva; Heitor Bernardes P. Delfino; Camila Toffoli-Ribeiro (LGBT Health, 2026)
Purpose: This study evaluated reproductive intentions, fertility-related knowledge, prior fertility counseling, and factors associated with reproductive intentions among transgender and nonbinary individuals receiving care at a Brazilian public reference center. Methods: This cross-sectional study with a qualitative component was conducted between July and November 2025 in a specialized gender-affirming care clinic in Brazil. Quantitative data included sociodemographic characteristics, reproductive history, gender-affirming hormone therapy (GAHT), and fertility-related variables. Logistic regression was used to assess factors associated with desire for future parenthood. Responses to a single open-ended question regarding perceived effects of GAHT on fertility were analyzed using thematic content analysis. Results: Eighty-two participants were included (mean age 27.5 ± 7.4 years). Most identified as transgender men (65.9%), followed by transgender women (26.8%) and nonbinary individuals (7.3%); 79.3% were receiving GAHT. Although 63.4% expressed a desire for future parenthood, only 7.3% had children. Current interest in fertility preservation was reported by 20.8% (15/72). Having children (adjusted odds ratio [aOR] = 0.03; 95% confidence interval [CI]: 0.001–0.62; p = 0.023) and each additional year of GAHT duration (aOR = 0.83; 95% CI: 0.70–0.99; p = 0.038) were associated with lower odds of desiring future parenthood. Sex assigned at birth was not independently associated with reproductive intentions. Qualitative analysis revealed misconceptions, uncertainty, and conditional beliefs regarding fertility. Conclusions: Desire for future parenthood was common among transgender and nonbinary individuals, whereas engagement with fertility preservation remained limited. These findings highlight the need for longitudinal, patient-centered reproductive counseling integrated into gender-affirming care.